HOW INTUITIVE IS OBJECT-ORIENTED DESIGN? - Hadar, Irit; Leron, Uri (Communications of the ACM, 2008)
The article discusses the object-oriented programming paradigm, which was created to deal with the increasing complexity of software systems. While object-oriented programming should theoretically be more intuitive than other forms of programming, recent studies show that it is often difficult to learn and practice. The authors document several difficulties related to the use of object-oriented design and use research from cognitive psychology to place these difficulties within a framework of intuitive and analytical modes of thinking.